"O primeiro contacto com a realidade do mundo escolar" - Diogo Manuel Duarte Seixas (2022)
The professional internship is characterized by the culmination of integral students' formation. This document describes the experiences throughout the process aiming to highlight the evolution as an intern student. It is the first time that the internal student has had real contact with the teaching world. During this contact, several moments are experienced. These moments end up tracing our identity as teachers and evidence our evolution based on learning, difficulties, adopted strategies, and solutions to become better teacher and person. The course began in September 2021 and was finished in June 2022, at the Cooperative School where I had the opportunity to teach a professional sports course. The document will be divided into five parts: The first one is the introduction that will contextualize the internship report, the second one includes the personal framework, where I will address my journey, the third one is about the framework of professional practice, which consists of the characterization of the school, the class, the Internship Center, the Cooperating Professor, and the Guiding Professor, the fourth point refers to the realization of professional practice, in which I will address the entire teaching-learning process throughout the school year, and finally, the fifth point, states the research study carried out.